Iron toxicity tolerance in rice: Roles of Auxins and Gibberellins - Daramola, O.S.; Shaibu, A.A.; Semwal, V.K. (Springer, 2022)
Rice is subjected to high iron (Fe) levels in acidic lowland soils which results in disturbance of basic metabolism, several changes in physiological processes and as a consequence reduction in productivity. In response to Fe toxicity in soils, rice like other plants produce a number of hormones (also known as phytohormones), including auxins, gibberellic acids and cytokinins. These hormones are organic substances that regulates plant growth and development, and play important role in rice defence against Fe toxicity. These hormones are part of signal-transduction pathway that stimulates reactions for Fe toxicity responses. The biosynthesis, transport, redistribution and conjugation of these plant hormones in rice has been shown not only to reduce high Fe inside rice plant tissue, but also to alleviate the adverse effect of Fe toxicity. In the present review, we discuss the conditions that enhances Fe toxicity in rice, effects of Fe toxicity in rice and tolerance strategies to Fe toxicity in rice. A special attention has been paid on the role and mechanism of phytohormones in enhancing tolerance and overcoming Fe toxicity-induced adverse effects